The strategic cost management and business value measurement models. case of decommoditization in the sector auto parts (Costos y Gestión, 2021)
The work presents the case of an Argentine SME, dedicated to the production and marketing of automotiveaccumulators, framed in strategic cost management. The market opportunities and the entrepreneurial profileof the owners, leads them to evaluate a strategic reformulation based on a strong increase in fixed coststhat will allow to efficient production, reducing variable costs, improving processes, reducing waste and obtaininga decommoditized product. This will result in a quantum leap in the positioning of the SME, preventingthe rest of the competitors from reaching it in the medium term, achieving a competitive advantage in thesector.Traditional tools such as the degree of operational lever were first used to assess the decision, however whenwe subject the analysis to models that measure the value added by the strategy to the SME, the results arevery different, even contradictory.Through case analysis, the work aims to generate a contribution to the strategic cost management of closedcapital SMEs, whose investments are tied to financing as they are developed in contexts with rationing funds,and in uncertain scenarios, proposing a five-step model (based on the flow of discounted funds), which allowsto calculate the impact that the strategy of dismodilization of products generates on the value of SMEs.Obviously, the measurement of the value created will vary from one SME to another, depending on the drivingstyle, human resources, the nature and diversity of the business portfolio, the degree of decentralizationof its size, its coverage, its clientele and the sense of urgency that exists in it; however, a tool that measuresstrategic impact will help make more rational decisions with more efficient allocation of resources.
Keywords: Operating leverage; Value created; Strategic cost management; Cash flow; Uncomoditize; Positioning